Diversity of Rabies Virus Variants in Insectivorous Bats (Chiroptera: Vespertilionidae and Molossidae): An Epidemiological Study in Central Argentine Patagonia - Analía L. Giménez; Marcelo J. Zabalza; Laura P. Novaro; Gabriela A. Centurion; Melanie Y. Barrios-Benito; Ivana Moncá; Fabricio Chaar Letourneau; Román Casanovas; Susana E. Russo (Viruses, 2025)
Rabies virus (RABV) causes a fatal infection in the central nervous system of mammals. RABV circulates through two different epidemiological cycles—terrestrial and aerial—with bats being the natural reservoir of the aerial cycle. In Patagonia, only variants (V) associated with insectivorous bats have been detected. The aim of this study was to assess the diversity of circulating RABV variants in bats from Central Patagonia, Argentina. Fifty-six samples of seven bat species from eleven localities in Chubut province were analyzed using a direct immunofluorescence and biological assay, while antigenic variants were determined using an indirect immunofluorescence test. Twelve samples tested positive for RABV (>21%). Variants V4 and V6 were identified in samples of T. brasiliensis and L. varius, respectively. The remaining positive samples did not exhibit any antigenic pattern previously identified in Argentina. These samples were associated with H. macrotus, H. magellanicus, H. montanus, and L. varius. Our results confirm RABV circulation in over 71% of the bat species analyzed and in over 63% of the localities assessed. We recommend maintaining active surveillance at both local and regional levels to ensure the early detection of cases and transmission risks, which is crucial for disease prevention and control.